Effect of low expression level of acetyl coenzyme A synthetase gene on secondary metabolite in Monascus - Lin Lin; Chundan Zhang; Xinman Shao; Pupin Liu; Zhangfei Wu; Yanxia Lu; Hongzhen Guo (Czech Journal of Food Sciences, 2022)
Acetyl-coenzyme A (CoA) is a key metabolite produced by the acetyl-CoA synthetase (ACS) gene in energy metabolism and biosynthetic pathways. ACS is speculated to be the branching site of monacolin K (MK) and citrinin production and related to the metabolite production of Monascus. In this study, the ACS expression was inhibited by ribonucleic acid interference (RNAi). T7 was selected for a follow-up analysis of the lowest ACS expression, which was 0.401 times higher than that of the wild-type strain. The effects on the colony morphology of Monascus were determined. The morphological characteristics of mycelia and spores were observed under a scanning electron microscope. The contents of secondary metabolites, namely, MK and citrinin, were determined through high performance liquid chromatography (HPLC). Colour values were measured with a spectrophotometer. Results showed that the low ACS expression could inhibit the growth of Monascus colonies and the hypha and affect the formation and morphology of Monascus M1 spores. It could also inhibit the production of the main secondary metabolites, namely, MK, citrinin, and pigment.